Hidrične epidemije v Sloveniji v letih 1981-2002 - Hojs, Ana (Zdravstveno varstvo, 2004)
Background: The review of waterborne outbreaks is lesson about microbiologicalagents, causes, measures and needs in the very important field of drinking water. Waterborne outbreaks are notifiable in Slovenia. Methods: In a descriptive study written waterborne outbreaks reports gathered through notification system were reviewed for the period 1981-2002. Results: From 1981-2002 nine health regions reported 78 waterborne outbreaks, affecting 6558persons, one person died. The microbe that caused the outbreak was identified for 45 of 78 outbreaks. Shigella sonnei was the agent most commonlyimplicated in outbreaks. Most outbreaks were associated with ingestionof water contaminated with sewerage or surface water, the next cause was: system was without chlorination or with intermittent chlorination. Most common selected control measure was disinfection. Conclusions: Waterborne outbreaks are still threat to public health. Decreased number of notified waterborne outbreaks could be misleading. Permanent control of risk factors inwater supply and corrective actions need to be taken.
Keywords: epidemije; infekcije; pitna voda; voda